Sitagliptin prevents aggravation of endocrine and exocrine pancreatic damage in the Zucker Diabetic Fatty rat - focus on amelioration of metabolic profile and tissue cytoprotective properties - Mega, C. (2015)
BACKGROUND: The purpose of this study was to investigate some of the possible mechanisms underlying the protective effects of a dipeptidyl peptidase IV (DPP-IV) inhibitor, sitagliptin, on pancreatic tissue in an animal model of type 2 diabetes mellitus (T2DM), the Zucker Diabetic Fatty(ZDF) rat, focusing on glycaemic, insulinic and lipidic profiles, as well as, on apoptosis, inflammation, angiogenesis and proliferation mediators. METHODS: Male obese diabetic ZDF (fa/fa) rats, aged 20 weeks, were treated with sitagliptin (10 mg/kg bw/day) during 6 weeks and compared to untreated diabetic and lean control littermates. Metabolic data was evaluated at the beginning and at the end of the treatment, including glycaemia, HbA1c, insulinaemia, HOMA-beta and TGs. Endocrine and exocrine pancreas lesions were assessed semiquantitatively by histopathological methods. Pancreas gene (mRNA) and protein expression of mediators of apoptotic machinery, inflammation and angiogenesis/proliferation (Bax, Bcl2, IL-1β, VEGF, PCNA and TRIB3) were analyzed by RT-qPCR and/or by immunohistochemistry. RESULTS: Sitagliptin treatment for 6 weeks (between 20 and 26 week-old) was able to significantly (p < 0.001) ameliorate all the metabolicparameters, by preventing the increase in blood glucose and in serum TGs contents (16.54% and 37.63%, respectively, vs untreated), as well as, by preventing the decrease in serum insulin levels and in the functional beta cells capacity accessed via HOMA-beta index (156.28% and 191.74%, respectively, vs untreated). Sitagliptin-treated diabetic rats presented a reduced pancreas Bax/Bcl2 ratio, suggestive of an antiapoptotic effect; in addition, sitagliptin was able to completely reduce (p < 0.001) the pancreas overexpression of IL-1β and TRIB3 found in the untreated diabeticanimals; and promoted a significant (p < 0.001) overexpression of VEGF and PCNA. CONCLUSION: In this animal model of obese T2DM (the ZDF rat), sitagliptin prevented β-cell dysfunction and evolution of pancreatic damage. The protective effects afforded by this DPP-IV inhibitor may derive from improvement of the metabolic profile (viewed by the amelioration of glucose and TGs levels and of insulin resistance) and from cytoprotective properties, such as antiapoptotic, anti-inflammatory, pro-angiogenic and pro-proliferative.